2012
DOI: 10.1080/19443994.2012.664377
|View full text |Cite
|
Sign up to set email alerts
|

Flood reduction analysis on watershed of LID design demonstration district using SWMM5

Abstract: 2012) Flood reduction analysis on watershed of LID design demonstration district using SWMM5, Desalination and Water Treatment, 38:1-3, 255-261, A B S T R AC TUrban development is the primary cause of the expansion of impervious areas. Urbanization reduces infi ltration of rainwater, increases runoff volume, and fi nally has an effect on the hydrological cycle and urban environment. To solve these problems, Low Impact Development (LID) methods have been used to restore the natural hydrology of predevelopment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 6 publications
0
11
0
4
Order By: Relevance
“…Lee et al (2012) found that the use of LID facilities in a demonstration district of AsanTangjung New Town can reduce the flood peak discharges of 50-and 100-year return periods by about 7e15% at a wider catchment scale. Holman-Dodds et al (2003) monitored disconnected impervious areas and recorded reduced runoff at the site, as compared to traditional development.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2012) found that the use of LID facilities in a demonstration district of AsanTangjung New Town can reduce the flood peak discharges of 50-and 100-year return periods by about 7e15% at a wider catchment scale. Holman-Dodds et al (2003) monitored disconnected impervious areas and recorded reduced runoff at the site, as compared to traditional development.…”
Section: Introductionmentioning
confidence: 99%
“…Lee ve diğ. [28] tarafından yapılan çalışmada kentleşme ile birlikte yüzeysel akış debisinin arttığı ve biyotutma, bitkisel kanal, geçirgen kaldırım, yeşil çatı ve yağmur tankı gibi DEK uygulamalarından sonra debinin azaldığı görülmektedir. Dolayısıyla DEK uygulamaları ile taşkın ve sel riskinin önlenmesine yönelik deneysel ve saha çalışmalarına ağırlık verilmelidir.…”
Section: Düşük Etkili Kentleşmenin Taşkın üZerindeki Etkisiunclassified
“…The results showed that the EBF model had the highest accuracy in predicting flood susceptibility within the catchment, in which 15% of the total areas were located in high and very high susceptibility classes, and 62% were located in low and very low susceptibility classes. These results can be used for the planning and management of areas vulnerable to floods in order to prevent flood-induced damage; the results may also be useful for natural disaster assessment.In recent years, many statistical and probabilistic models have been tested to prepare flood susceptibility maps [9,10]. Geographic Information System (GIS) has been used as an effective tool for spatial analysis and data manipulation due to its ability to handle large amounts of spatial data [11].…”
mentioning
confidence: 99%